Mugabe power and plunder in Zimbabwe - Meredith, Martin (Oxford PublicAffairs, 2002)
Robert Mugabe was once hailed around the World as a revolutionary hero. After a fierce civil war against white minority rule in Rhodesia, he emerged as the new leader of the country now called Zimbabwe, advocating reconciliation and and racial harmony. Hopes were high that Mugabe had the intelligence, political savvy, and idealistic vision to overcome legacy of war and forge ahead with economic and social development. As Western governments lined up with promises of aid, Zimbabwe, at independence in 1980, seemed destined for era of peace and prosperity. The honeymoon did not last long. Determined to gain total power through a one-party system, Mugabe unleashed an unending campaign of mass murder and terror against his political opponents. Today, Zimbabwe is a country beset by violence and lawlessness. Its economy is in tatters;its people starving. In Mugabe, renowned Africa expert Martin Meredith pieces together the riveting and tragic political story of what happened to Zimbabwe and to a leader who once represented one the world's best hopes for a democratic Africa.
Includes bibliographical references (p. [229]-231)
Keywords: Mugabe, Robert Gabriel, 1924- Zimbabwe-Politics and government-1980 Zimbabwe-Social conditions-1980